2019
DOI: 10.1080/02640414.2019.1690618
|View full text |Cite
|
Sign up to set email alerts
|

Footwear insoles with higher frictional properties enhance performance by reducing in-shoe sliding during rapid changes of direction

Abstract: A novel 3D motion capture analysis assessed the efficacy of insoles in maintaining the foot position on the midsole platform inside the shoe during rapid change of direction manoeuvres used in teams sports. An insole (TI) with increased static (35%) and dynamic (49%) coefficient of friction compared to a regular insole (SI) were tested. Change of direction performance was faster (p < .001) and perceived to be faster (p < .001) in TI compared to SI. Participants utilised greater coefficient of friction in TI co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Contact forces at the foot-upper interface could be used to measure the non-slip function of socks. Previous studies have shown greater foot motion on an insole with socks having lower friction [ 4 , 15 ], suggesting that the inner wall of the upper may experience contact force at the foot-upper interface. Based on the observation, the current study installed pressure sensors by minimally cutting the upper to measure the foot slip, which is not visible from the outside.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contact forces at the foot-upper interface could be used to measure the non-slip function of socks. Previous studies have shown greater foot motion on an insole with socks having lower friction [ 4 , 15 ], suggesting that the inner wall of the upper may experience contact force at the foot-upper interface. Based on the observation, the current study installed pressure sensors by minimally cutting the upper to measure the foot slip, which is not visible from the outside.…”
Section: Discussionmentioning
confidence: 99%
“…The method suggested in this study may be a cost-effective option that minimizes the effects of skin artifacts and changes in shoe integrity. Previous studies have made holes in the shoe upper to observe foot motion inside shoes [ 4 , 15 ], which may affect the shoe elasticity [ 17 ]. The altered elasticity would affect the amounts of foot slip during acute maneuvers so that it would be unable to measure the non-slip function of socks in an intact shoe condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sock and shoe developers need to quickly measure the frictional properties of their prototypes while developing new socks or insoles targeting a specific population, such as patients with diabetes and athletes. For example, basketball players may need to wear socks with higher friction to produce acute movements such as cutting [ 31 ] while long-distance runners may wear socks with less friction for preventing blisters [ 32 ]. Acrylic was used to manufacture the ramp surface on which other types of socks (e.g., different non-slip pads, fabric compositions) can be attached easily so that the developers may use this protocol to manufacture socks specific to a situation.…”
Section: Discussionmentioning
confidence: 99%
“…The last weight may not represent the normal force applied to the feet in daily life and sports. The last weight was around 200 N (20 kg), lower than normal forces (1000 N to 2000 N) observed in sports requiring acute directional changes such as side-cut and turning tasks [ 31 ] and even in walking on a flat surface with a preferred speed (e.g., less than 1000 N) [ 33 ]. Previous studies have reported that greater applied weights (greater normal force) can reduce the coefficient of friction at the contact interface [ 10 , 34 ], suggesting that the findings in the current study may not be generalizable for estimating COF values with greater normal forces.…”
Section: Discussionmentioning
confidence: 99%